E-Research Collaboration and the Free-Rider Problem: Communication Solutions to Social Dilemmas in Computer Mediated Research Collaborations - BALLIET, Daniel Patrick (Institutional Knowledge at Singapore Management University, 2010)
Collaborative scientific projects can be considered public goods dilemmas. This is a particular type of social dilemma, where short-term immediate self-interests are at odds with long-term collective benefits. Perhaps the best known solution to the free-rider problem in social dilemmas is communication between participants prior to making contributions to the public good. However, there is research to suggest that people contribute less to public goods while communicating on-line before the dilemma, as opposed to face-to-face discussion. This chapter will discuss why computer-mediated mediums of communication are less effective at improving cooperation amongst collaborators (e.g., lack of social cues to examine the credibility of commitment, less leadership, and poorer monitoring of other’s behavior) and propose several means for addressing this challenge to on-line collaborations (e.g., videoconference, telephone communication, prior face-to-face interactions, frequent coordinated communications, and reputation evaluations).